Comparative Analysis of Hybrid-Electric Regional Aircraft with Tube-and-Wing and Box-Wing Airframes: A Performance Study - Giuseppe Palaia; Karim Abu Salem; Alessandro A. Quarta (Applied Sciences, 2023)
The continuously expanding transport aviation sector has a significant impact on climate change, and measures must be taken to limit its environmental impact. The study of advanced airframes, which may increase the lift-to-drag ratio and structural efficiency, and the development of innovative high-efficient powertrains, could be a way to achieve air transport decarbonization. This paper explores this broad topic by proposing a classical performance comparison between an aircraft with a traditional tube-and-wing (TW) airframe and a corresponding one with an advanced box-wing (BW) lifting architecture, both equipped with a parallel hybrid-electric powertrain. In fact, the propulsion technologies selected for this comparative study are consistent with the 2035 forecast, and both aircraft concepts are designed to belong to the regional transport category. The comparison between TW and BW is conducted on a conceptual and multi-disciplinary level, offering an analysis of the competitive benefits and limitations in terms of the aerodynamic, structural, and propulsive performance of the two configurations. The metrics selected to make the comparison are related to aircraft performance, such as the structural weight, the block fuel, or the energy required to accomplish the assigned mission. The outcomes obtained highlight the potential of BW airframes coupled with hybrid-electric powertrains to reduce fuel consumption, and hence the related greenhouse gas emissions, because of improvements introduced by this advanced architecture in both the aircraft’s empty weight and energy efficiency.